Impact of drug distribution into adipose on tissue function: The cholesteryl ester transfer protein (CETP) inhibitor anacetrapib as a test case - Douglas G. Johns; Sheng‐Ping Wang; Raymond Rosa; James Hubert; Suoyu Xu; Ying Chen; Thomas Bateman; Robert O. Blaustein (Wiley, 2019)
Abstract Anacetrapib is an inhibitor of cholesteryl ester transfer protein (CETP) previously under development as a lipid‐modifying agent that reduces LDL‐cholesterol and increases HDL‐cholesterol in hypercholesterolemic patients. Anacetrapib demonstrates a long terminal half‐life and accumulates in adipose tissue, which contributes to a long residence time of anacetrapib. Given our previous report that anacetrapib distributes into the lipid droplet of adipose tissue, we sought to understand whether anacetrapib affected adipose function, using a diet‐induced obese (DIO) mouse model. Following 20 weeks of treatment with anacetrapib (100 mg/kg/day), levels of the drug increased to approximately 0.6 mmol/L in white adipose tissue. This level of anacetrapib was not associated with any impairment in adipose functionality as evidenced by a lack of any reduction in biomarkers of adipose functionality (plasma adiponectin, leptin, insulin; adipose adiponectin, leptin mRNA). In DIO wild‐type (WT) mice treated with anacetrapib for 2 weeks and then subjected to 30% food restriction during washout to induce weight loss (18%) and fat mass loss (7%), levels of anacetrapib in adipose and plasma were not different between food restricted and ad lib‐fed mice. These data indicate that despite deposition and long‐term residence of ~0.6 mmol/L levels of anacetrapib in adipose tissue, adipose tissue function appears to be unaffected in mice. In addition, these data also indicate that even with severe caloric restriction and acute loss of fat mass, anacetrapib does not appear to be mobilized from the fat depot, thereby solidifying the role of adipose as a long‐term storage site of anacetrapib.